Dynamic mitigation of the tearing mode instability in a collisionless current sheet - Yan-Jun Gu; Shigeo Kawata; Sergei V. Bulanov (Scientific Reports, 2021)
Abstract Dynamic mitigation for the tearing mode instability in the current sheet in collisionless plasmas is demonstrated by applying a wobbling electron current beam. The initial small amplitude modulations imposed on the current sheet induce the electric current filamentation and the reconnection of the magnetic field lines. When the wobbling or oscillatory motion is added from the electron beam having a form of a thin layer moving along the current sheet, the perturbation phase is mixed and consequently the instability growth is saturated remarkably, like in the case of the feed-forward control.